UJI AKTIVITAS ANTIOKSIDAN CESSA STERA WEDANG HERBAL TANPA GULA (ANTIOXIDANT ACTIVITY TEST OF CESSA STERA AS HERBAL DRINK WITHOUT SUGAR) - Marsandah, Marsandah; Musfira, Ainun; Agustina, Ayu Safitri; Karneng, Syahdam (Indonesian Journal of Pure and Applied Chemistry, 2024)
This study aims to evaluate the antioxidant content and organoleptic properties of herbal tea using a mixture of secang wood and stevia leaves. The sample preparation method involves separation based on wetness level, washing, drying, and grinding to powder. Phytochemical tests showed the presence of flavonoids, saponins, alkaloids, tannins, terpenoids and steroids in both samples. The water content test shows the value is in accordance with the quality standards for packaged dry tea. Antioxidant activity was tested using the DPPH method, and the herbal wedang formulation with a proportion of 1:1 (FIII) showed the highest antioxidant activity of 76%. Organoleptic tests showed that the panelists really liked the color, aroma and taste of the FIII formulation. The overall results show that the FIII formulation is the best choice with high antioxidant content and good acceptance from consumers.